2017
DOI: 10.1038/s41598-017-09257-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of RAGE in substantia nigra of rats blocks 6-OHDA–induced dopaminergic denervation

Abstract: The receptor for advanced glycation endproducts (RAGE) is a pattern-recognition receptor associated with inflammation in most cell types. RAGE up-regulates the expression of proinflammatory mediators and its own expression via activation of NF-kB. Recent works have proposed a role for RAGE in Parkinson’s disease (PD). In this study, we used the multimodal blocker of RAGE FPS-ZM1, which has become available recently, to selectively inhibit RAGE in the substantia nigra (SN) of rats intracranially injected with 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 34 publications
1
29
1
1
Order By: Relevance
“…Conflicting findings on RAGE biology subsist in PD studies, however, it has been described that PD patients’ brains have increased expression of RAGE paralleled with AGEs accumulation, and that RAGE activation was linked to oxidative stress ( Dalfó et al, 2005 ; Ding and Keller, 2005 ; Sathe et al, 2012 ). Additionally, RAGE up-regulation and activation was also demonstrated in sub-acute MPTP, rotenone and 6-OHDA mice models of PD ( Teismann et al, 2012 ; Abdelsalam and Safar, 2015 ; Gasparotto et al, 2017 ). On the other hand, ablation of RAGE protects primary dopaminergic neurons against MPP + induced toxicity ( Teismann et al, 2012 ), and selective inhibition of RAGE prevented dopaminergic denervation and locomotory and exploratory deficits induced by 6-OHDA in rats ( Gasparotto et al, 2017 ).…”
Section: Glycation In Parkinson’s Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…Conflicting findings on RAGE biology subsist in PD studies, however, it has been described that PD patients’ brains have increased expression of RAGE paralleled with AGEs accumulation, and that RAGE activation was linked to oxidative stress ( Dalfó et al, 2005 ; Ding and Keller, 2005 ; Sathe et al, 2012 ). Additionally, RAGE up-regulation and activation was also demonstrated in sub-acute MPTP, rotenone and 6-OHDA mice models of PD ( Teismann et al, 2012 ; Abdelsalam and Safar, 2015 ; Gasparotto et al, 2017 ). On the other hand, ablation of RAGE protects primary dopaminergic neurons against MPP + induced toxicity ( Teismann et al, 2012 ), and selective inhibition of RAGE prevented dopaminergic denervation and locomotory and exploratory deficits induced by 6-OHDA in rats ( Gasparotto et al, 2017 ).…”
Section: Glycation In Parkinson’s Diseasementioning
confidence: 91%
“…RAGE is a multi-ligand receptor of the immunoglobulin superfamily of cell surface molecules with a crucial role in the CNS in neuroinflammation, oxidative stress and neurotoxicity ( Ding and Keller, 2005 ). In the CNS RAGE is found in neurons, microglia, astrocytes, and brain endothelial cells ( Ding and Keller, 2005 ; Deane et al, 2012 ; Teismann et al, 2012 ; Gasparotto et al, 2017 ). Typically, after ligand binding RAGE induces the activation of the transcription factor nuclear factor-kappa B (NF-κB) ( Bierhaus et al, 2001 ; Angelo et al, 2014 ; Tóbon-Velasco et al, 2014 ) ( Figure 2 ).…”
Section: Glycation In Parkinson’s Diseasementioning
confidence: 99%
“…The following synthetic collagen-mimetic peptides were synthesised in the laboratory of Professor Richard Farndale (University of Cambridge, U.K.): collagen-related peptide (CRP: sequence = GCO(GPO) 10 GCOG-NH 2 , O = hydroxyproline); cross-linked CRP (CRPXL); GPP (sequence = GPC(GPP) 10 GPC-NH 2 ); and GFOGER (sequence = GPC(GPP) 5 GFOGER(GPP) 5 GPC-NH 2 ) 30 . Antibodies against phospho-SFK (Y416) (#2101 S) 52 , Src (#2108 S) 52 and phospho-PLCγ2 (Y1217) (#3871) 53 were from Cell Signalling Technology (Danvers, MA, U.S.A.). Antibodies against LAT (#06-807) 54 and phospho-tyrosine (4G10) (#05-321) 55 were from Millipore (Watford, U.K.).…”
Section: Methodsmentioning
confidence: 99%
“…First, the same AGER rs2070600 SNP that was implicated in CA1 atrophy during AD, was also correlated to the highest risk for PD development of all known AGER SNPs in a Turkish cohort GWAS (N=174 PD patients and N=150 healthy controls) [89]. In addition, when compared to healthy controls, PD patients have recently been shown to possess higher concentrations of RAGE ligands S100B and HMGB1 in the substantia nigra and cerebral spinal fluid (CSF) [90][91][92]. In rodent models, numerous studies have indicated that animals derive prominent protection from PD-like impairments when RAGE signaling was blocked through genetic ablation of S100b/Ager or by the administration of a RAGE inhibitor, FPS-ZM1, a BBB permeable, high affinity, multimodal blocker of RAGE [90].…”
Section: Rage and Parkinson's Disease Another Manifestation Of Cellumentioning
confidence: 99%
“…In addition, when compared to healthy controls, PD patients have recently been shown to possess higher concentrations of RAGE ligands S100B and HMGB1 in the substantia nigra and cerebral spinal fluid (CSF) [90][91][92]. In rodent models, numerous studies have indicated that animals derive prominent protection from PD-like impairments when RAGE signaling was blocked through genetic ablation of S100b/Ager or by the administration of a RAGE inhibitor, FPS-ZM1, a BBB permeable, high affinity, multimodal blocker of RAGE [90]. Either strategy was sufficient to abrogate a variety of impairments observed in the PD-like rodent models, such as apoptosis of dopaminergic cells; locomotor defects; neuroinflammatory microgliosis and astrogliosis, as measured by increased ionized calcium binding adaptor molecule 1 (IBA1) and glial fibrillary acidic protein (GFAP) staining, respectively; tyrosine hydroxylase (and therefore dopamine) deficits; NF-K B activation; and tumor necrosis factor alpha (TNFα) upregulation in the presence of PD-like syndromes induced by toxins.…”
Section: Rage and Parkinson's Disease Another Manifestation Of Cellumentioning
confidence: 99%